2022
DOI: 10.3390/en15093159
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Wind Energy Potential Using Efficient Global Optimization: A Case Study for the City Gdańsk in Poland

Abstract: Wind energy (WE), which is one of the renewable energy (RE) sources for generating electricity, has been making a significant contribution to obtaining clean and green energy in recent years. Fitting an appropriate statistical distribution to the wind speed (WS) data is crucial in analyzing and estimating WE potential. Once the best suitable statistical distribution for WS data is determined, WE potential and potential yield could be estimated with high accuracy. The main objective of this paper is to propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Authors concluded that new forms of governance are necessary to implement innovative strategies and new business models, allowing for the development of innovative approaches such as PEDs. Similarly, an analysis of the wind energy potential for Gdansk (Poland) was developed in Aydin et al [53]. The analysis considered the installation of innovative city-type wind turbines to generate electricity for the city.…”
Section: The Case Of Megacitiesmentioning
confidence: 99%
“…Authors concluded that new forms of governance are necessary to implement innovative strategies and new business models, allowing for the development of innovative approaches such as PEDs. Similarly, an analysis of the wind energy potential for Gdansk (Poland) was developed in Aydin et al [53]. The analysis considered the installation of innovative city-type wind turbines to generate electricity for the city.…”
Section: The Case Of Megacitiesmentioning
confidence: 99%
“…It has a good renewable source and hosts the second largest solar renewable energy project in Al-Rass, with a total capacity of 700 MW, as listed in Table 1. The Qassim region has been tested with encouraging results for solar power systems [24,25] based on data on global horizontal irradiance, direct normal irradiance, diffuse irradiance, ambient temperature, humidity, atmospheric pressure, and wind speed for the month of August 2014. In this paper, wind systems will be discussed to study this area for the purpose of building a wind turbine farm to produce electricity.…”
Section: -2-qassim Region Energy Scenariomentioning
confidence: 99%
“…Matching the appropriate statistical distribution to the wind speed (WS) data is crucial in analyzing and estimating the EC potential. In the paper [33] the efficient global optimization (EGO) technique to fit the statistical distribution to WS data were proposed, and the technique performance was compared to the genetic algorithm (GA), simulated annealing (SA), and differential evolution (DE). On the basis of Weibull parameters, the authors obtained the potential of the EC and the potential annual revenues for Gda ńsk (Pomerania Voivodeship, Poland).…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%